Planning and postponing the urban reform of Coimbra’s downtown - Calmeiro, Margarida (International Planning History Society Proceedings, 2016)
In this communication I intend to analyse the process of transformation and modernization of Coimbra’s downtown neighbourhood, firstly carried out to face the recurrent flooding of the Mondego’s river but moreover as a beautification plan within the European models. After several attends to minimize recurrent floods, only the development of science and technology during the nineteen century made possible the construction of a new river bank and consequently a set of reform projects planning a new regular and wealthy neighbourhood. Coimbra was a middle size city nevertheless, until the beginning of the twenty century, it was the settlement of the only Portuguese University, fact that gave the city a huge importance not only within the country but also in the empire. However like all Portuguese cities in this period, Coimbra faced several sanitary problems due to the absence of a water and sewer network, lighting infrastructures or public transports, in addition in Coimbra these problems were enlarged by the recurrent floods. The solution was the construction of a new bank planned and executed by the state engineers but partial paid by the municipality. The construction of the new river front endorsed the reform of the main city entrance, the construction of a new bridge and a square, the enlargement of the Main Street and the construction of a boulevard by the river. Moreover this plan required the skills of a new technician, the first municipal engineer. Few years after, the riverfront and the image of Coimbra were once more reconfigured to implant the new train station and a new train line to the interior of Portugal, increasing the embankment 38 meters into the river. With this project began a new phase of planning that spans until nowadays. It started with the opening of a boulevard connecting the station and the town hall then in the begging of the twenty century, within the principles in vogue in Europe, the plan was extended proposing a set of wide avenues to sanitize the old unhealthy neighbourhood, emulating Haussmann’s model to Paris. However financial difficulties and lack of government support postponed this ambitious plan nevertheless it was not overlooked, being followed by a succession of plans and becoming a part of the collective imagination. This paper analyses this set of plans, its motivations and its relation with the international models. Nevertheless it also explores its process, emphasizing the role of the population yearning for the reform of the old core and the municipal council’s efforts to execute these plans. Furthermore stress the consequences of these unrealized plans for the transformation and grow of the rest of the city.